Health status in the ambulance services: a systematic review - Hem Erlend; Ekeberg Øivind; Sterud Tom (BMC, 2006)
Abstract Background Researchers have become increasingly aware that ambulance personnel may be at risk of developing work-related health problems. This article systematically explores the literature on health problems and work-related and individual health predictors in the ambulance services. Methods We identified the relevant empirical literature by searching several electronic databases including Medline, EMBASE, PsychINFO, CINAHL, and ISI Web of Science. Other relevant sources were identified through reference lists and other relevant studies known by the research group. Results Forty-nine studies are included in this review. Our analysis shows that ambulance workers have a higher standardized mortality rate, higher level of fatal accidents, higher level of accident injuries and a higher standardized early retirement on medical grounds than the general working population and workers in other health occupations. Ambulance workers also seem to have more musculoskeletal problems than the general population. These conclusions are preliminary at present because each is based on a single study. More studies have addressed mental health problems. The prevalence of post-traumatic stress symptom caseness was > 20% in five of seven studies, and similarly high prevalence rates were reported for anxiety and general psychopathology in four of five studies. However, it is unclear whether ambulance personnel suffer from more mental health problems than the general working population. Conclusion Several indicators suggest that workers in the ambulance services experience more health problems than the general working population and workers in other health occupations. Several methodological challenges, such as small sample sizes, non-representative samples, and lack of comparisons with normative data limit the interpretation of many studies. More coordinated research and replication are needed to compare data across studies. We discuss some strategies for future research.